Pengaruh Corporate Governance Terhadap Manajemen Laba dengan Media Coverage sebagai Variabel Moderasi - Deza, Aldo Dwinanda; Afriyenti, Mayar (Universitas Negeri Padang, 2025)
This study aims to examince the impact of corporate governance on earnings management with media coverage as moderating variables. The theoretical foundation used in this research is the agency theory. This type of research is causal study that uses a quantitative approach. Using purposive sampling, 100firm-year observations of BUMN companies listed on the Indonesia IDX from 2019 to 2023 were analyzed. The statistical method used in this study is panel regression analysis with a Random Effect Model using eViews version 12. The results show that Corporate Governance has no significant effect on earnings management. In addition, the results of this study indicate that media coverage does not significantly moderate the relationship between corporate governance and earnings management.